Port site recurrence of esophageal adenocarcinoma after minimally invasive esophagectomy: a case report - Taichi Horino; Yoshifumi Baba; Daichi Nomoto; Kazuto Harada; Yukiharu Hiyoshi; Yohei Nagai; Masaaki Iwatsuki; Shiro Iwagami; Yuji Miyamoto; Naoya Yoshida; Hideo Baba (Surgical Case Reports)
Abstract Background Port site recurrence has been observed after a variety of oncologic resection procedures. However, few have reported port site recurrence of esophageal cancer. Case presentation A 51-year-old man underwent minimally invasive esophagectomy for pT3(AD)N3M0 adenocarcinoma of the esophagus. One year after surgery, he presented with a rapidly growing tumor on the right thoracic wall. Contrast computed tomography demonstrated an enhancing tumor with uptake on positron emission tomography. We performed resection of the thoracic wall, including the skin and subcutis. The pathologic diagnosis was poorly differentiated adenocarcinoma, consistent with metastasis of esophageal origin. Conclusion This was the first report on thoracic port site recurrence of esophageal adenocarcinoma. We recommend elimination of leakage around the thoracoscopic ports to prevent such recurrence. We should provide prudent postoperative clinical surveillance.